Emosi Remaja Putri yang Mengalami Dismenore di Wilayah Desa Rajawetan Kecamatan Pancalang Kabupaten Kuningan - Marisa, Dewi Erna; Kasmad, Kasmad; Purbaningsih, Endah Sari (Cerdika: Jurnal Ilmiah Indonesia, 2022)
In adolescent girls, the maturity of the reproductive organs is marked by the presence of menstruation which is marked by dysmenorrhea. Dysmenorrhea is menstrual pain characterized as brief pain before or during menstruation, this pain lasts for one to several days during menstruation. Emotion refers to a characteristic feeling and thought, a biological and psychological state, and a set of tendencies to act. This study aims to determine the relationship between dysmenorrhea and emotion in adolescent girls in the Rajawetan Village, Pancalang District, Kuningan Regency. This research method uses correlational descriptive, with a cross-sectional research design. The population is young women in the Rajawetan Village area, Pancalang district, Kuningan Regency and the number of samples is 38 young women. The sampling technique used was total sampling. Instruments used in the form of observation sheets, and questionnaires. Data analysis used the Spearman Rank test with a value (p value = 0.000; = 0.05, r = - 0.645). The results of the univariate analysis of dysmenorrhea with no pain were 1 respondent (2.6%), mild pain was 11 respondents (28.9%), moderate pain was 13 respondents (34.2%), severe pain was 11 respondents (28.9%), severe pain was not controlled as many as 2 respondents (5.3%) and negative emotions as many as 15 respondents (39.5%), positive emotions as many as 23 respondents (60.5%). Bivariate analysis with Spearman Rank test obtained p-value = 0.000 <0.05 and correlation coefficient -0.645 then H0 is rejected, which means that there is a moderate and negative relationship between the variable dysmenorrhea and emotion in adolescent girls in the Rajawetan Village, Pancalang District, Kuningan Regency.